1994
DOI: 10.1159/000187829
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Urea Distribution Volume in Hemodialysis

Abstract: According to the urea kinetic model it is considered that the urea distribution volume (V) is that of body water, and that it is distributed in only one compartment. Since the V value is difficult to measure, it is normal to use 58% of body weight, in spite of the fact that it may range from 35 to 75%. In this study, we have calculated the value of V by using an accurate method based on the total elimination of urea from the dialysate. We have studied the V, and also whether the different dialysis characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
2
4
1
Order By: Relevance
“…Similar to previous reports [23, 24, 25]differences were found between the V obtained by the single-pool and the double-pool model; these differences may be explained by the fact that in a two-compartmental system, one compartment is cleared faster than the other. It is therefore necessary to wait for the reestablishment of urea equilibrium between compartments to determine V accurately.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous reports [23, 24, 25]differences were found between the V obtained by the single-pool and the double-pool model; these differences may be explained by the fact that in a two-compartmental system, one compartment is cleared faster than the other. It is therefore necessary to wait for the reestablishment of urea equilibrium between compartments to determine V accurately.…”
Section: Discussionsupporting
confidence: 90%
“…Two points o f discrepancy exist between our data and those of Maduell et al [ 1 ]. The first is the nonconstant V value in our pa tients.…”
contrasting
confidence: 99%
“…patient 1 of our series had a range from 40.8 to 63.8. i.e. a value of 23), we found that the mean value in our 12 patients was 17.4 ± 10.1 versus 4.8 ± 1.5 of the 35 patients of Maduell et al [1] (F 53.08. p < 0.0001). The reason for this dis crepancy is far from being clear.…”
mentioning
confidence: 42%
See 1 more Smart Citation
“…When ignored, PDUR can induce an overestimation of dialysis and nutritional indexes. The Kt/V can be overestimated by an average of 15-40% in a conventional 3-to 5-hour dialysis [6,8,9,12,[14][15][16] and the normal protein catabolic rate nPCR can be overestimated by 6-10% [4,17,18]. In our center, long 8-hour dialysis has been in use for more than 30 years with high-dialysis indexes based on pre-and immediate postdialysis urea samples.…”
Section: Introductionmentioning
confidence: 99%